2015
DOI: 10.5539/gjhs.v7n4p367
|View full text |Cite
|
Sign up to set email alerts
|

Personal, Familial and Environmental Determinants of Drug Abuse: A Causal-Comparative Study

Abstract: Aims:Two purposes were followed in this study: 1) comparing case and control group in eight factors separately and 2) performing a multivariate analysis for identifying risk and protective factors in relation to drug abuse.Methods:A casual-comparative study was conducted to investigate the study goals. Fifty Cases in a convenient sampling of addicts referring to addiction withdrawal centers and fifty eligible controls (recruited in a randomly sampling) were identified. One-sample independent T-Test for a univa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 16 publications
1
6
0
3
Order By: Relevance
“…Consistent with study findings by Njoki, (2013); Simatwa et al, (2014); Sajjadi et al, (2015); Shahraki et al, (2019), students who received unnecessary generous amount of pocket money were also more likely to abuse drugs and substance abuse compared to those who never received any because they have more cash at hand which they use to buy these drugs or even join other friends at entertainment joints where drugs and other substances are served without supervision.…”
Section: Household Economic Predictorssupporting
confidence: 84%
See 1 more Smart Citation
“…Consistent with study findings by Njoki, (2013); Simatwa et al, (2014); Sajjadi et al, (2015); Shahraki et al, (2019), students who received unnecessary generous amount of pocket money were also more likely to abuse drugs and substance abuse compared to those who never received any because they have more cash at hand which they use to buy these drugs or even join other friends at entertainment joints where drugs and other substances are served without supervision.…”
Section: Household Economic Predictorssupporting
confidence: 84%
“…For instance, a substantial number of students aged 13 -17 years in several national and private schools in Kuala Lumpur, Selangor, and Negeri Sembilan admitted that they are drug abusers. Most of these students come from middle and upper class families hence given unnecessary generous amount of pocket money per month which they use to easily obtain illegal drugs (Sajjadi et al, 2015;Shahraki et al, 2019). Similarly in Kenya, studies have revealed that family economic set up of a child influences his/her habits in that, students who receive more pocket money tend to engage more in drug abuse to an extent of converging with friend for alcoholic drinks during weekends and holidays than their counterparts who get less pocket money (Njoki, 2013;Simatwa et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Os profissionais de saúde devem participar ativamente dos programas e projetos de promoção da saúde (inclusive dentro das empresas), visando à prevenção do consumo de drogas. A ação educativa em saúde envolve profissionais, instituições, clientela, família e comunidade, devendo ter foco não apenas nas drogas ilícitas, mas, principalmente, no álcool e no tabaco, que, por serem drogas lícitas, tem seu consumo facilitado e são grandes responsáveis pelas maiores morbimortalidade e complicações clínicas, psicológicas, familiares e sociais (19,20) .…”
Section: Discussionunclassified
“…Os resultados deste estudo podem ser úteis para as empresas do setor metal mecânico e metalúrgico, que empregam grande número de trabalhadores e desejam colocarem prática programas preventivos, que permitam a avaliação do impacto das medidas adotadas para o controle do tabagismo e do alcoolismo. Para a enfermagem, este estudo aponta a necessidade de a equipe visualizar o ambiente de trabalho como um todo, e não somente estabelecer seu foco nos riscos ocupacionais clássicos ou no tratamento de saúde dos usuários de álcool e tabaco, mas voltando seu olhar à população masculina no ambiente de trabalho e a suas ações, possibilitando a diminuição do uso destas substâncias e o aumento da segurança e da saúde, beneficiando-se de comportamentos preventivos para sua saúde (3,20) .…”
Section: Discussionunclassified
“…In explaining the finding that IMT affects frustration reactivity in drug addicts, it should be noted that these individuals usually feel excessive frustration but only limited responsibility (41). Immediately they face even the most trivial obstacle, they feel serious distress.…”
mentioning
confidence: 99%